Pengaruh Model Take and Give Berbantuan Media Flashcard Pada Pembelajaran IPAS Terhadap Hasil Belajar Siswa Kelas 3 Sekolah Dasar - Nihayatus Sa'adah; Eni Nurhayati; Mochammad Ludfy Hadis Maqfiro (Universitas Islam 45 Bekasi, 2025)
This study aims to determine the effect of the Take and Give model assisted by flashcards on IPAS learning outcomes in third grade elementary school. This study is based on the need for interactive and effective teaching methods to improve student learning outcomes, especially in the IPAS teaching environment in the fundamental phase of education. This study applied a quantitative method with a quasi-experimental design, involving third-grade students at SDN Bluru Kidul 2. Data collection was obtained through observation of student activities, student learning outcomes, and student response questionnaires. The data were analyzed using simple regression tests, n-gain tests, and student response analysis. The results of the study showed a significant and positive effect of the Take and Give model with flashcard media on IPAS learning outcomes, with an increase in the experimental group with an average of 86.57%, which was higher and more effective than the control group with an average of 70.11%. Additionally, students demonstrated a positive response to this teaching model, as evidenced by an average student response rate of 80.4%. This indicates that the Take and Give model supported by flashcards can be an effective option for enhancing learning outcomes while motivating active student participation in learning activities.